OINAMIKA HARlAN HASIL TANGKAPAN RAJUNGAN (Portunnus pelagicus) KAITANNYA OENGAN FASE BULAN OI PERAIRAN BONDET,OREBON (The Daily Catch Dinamic ofBlue Flying Crab (Portunnus pewgicus) with its in Rewtionship to the Moon's Cycle in Bondet Waters, Cirebon) - Eko Sri Wiyono (Buletin PSP, 2007)
In arder to have better understanding about small scale fisheries characteristic, the study about reliltionship between moon's cycle and daily dynamic ofblue swimming crab (Portunnus pelilgicus) has conducted in Bandet, Cirebon. The study has carried out by following fishermen fishing activity during 28 days moon's cycle. The result shows that the catch of blue swimming crab (in number) is highest during full moon's cycles than others. However, individual weight of blue swimming crab is highest during new moon's cycles than others. The other result also sJwws that sex-ratio of blue swimming crab is lowest during dark moon's cycles than others.Keywords: blue flying crab, daily catch dynamic, moon's cycle.